PERBEDAAN KADAR SENG (ZN) RAMBUT BERDASARKAN DERAJAT STUNTING PADA ANAK USIA 6-9 TAHUN - Rahmawati, Arindha; Wirawanni, Yekti (Departemen Ilmu Gizi, Fakultas Kedokteran, Universitas Diponegoro, 2012)
Background: Stunting is a linear growth disorders are caused by chronic malnutrition especially zinc deficiency. Hair zinc concentrations can describe zinc status in the long term. The aim of this study is to investigate difference hair zinc concentrations based on degree of stunting in 6-9 years old children.Method: This cross sectional study was carried out on 57 school children aged 6-9 years. The subjects were chosen by stratified random sampling. Assessment degree of stunting are expressed by Height for Age Z-score (HAZ). Hair zinc concentrations was measured by Atomic Absorption Spectrophotometry (AAS) methods, the hair zinc concentrations less than 70 ppm was considered as chronic zinc deficiency. Bivariate analysis was using Kruskal Wallis, Mann-Whitney and Rank Spearman.Results: The prevalence of nonstunting (-1≤HAZ<2 SD), mild stunting (-2≤HAZ<-1 SD), moderate stunting (-3≤HAZ<-2 SD), and severe stunting (HAZ<-3SD) was 38,6%, 33,3%, 22,8%, and 5,3%, respectively. The median value hair zinc concentrations were 579,13 ppm. Out of 57 subjects, 26,3% had normal hair zinc concentrations, 73,7% had excess hair zinc concentrations, and no subject that experience of zinc deficiency. There is a significant difference on hair zinc concentrations based on degree of stunting (p=0,010) and positive correlation between hair zinc concentrations with Height for Age Z-score (HAZ) (r=0,303 ; p=0,022).Conclusion : There is a significant difference between hair zinc concentrations based on degree of stunting and significant correlation between hair zinc concentrations with Height for Age Z-score (HAZ). Hair zinc concentrations increased with increasing Height for Age Z-score (HAZ).Keywords : Degree of stunting, Height for Age Z-score (HAZ), Hair zinc concentrations, malnutrition, children